2013
DOI: 10.3892/mmr.2013.1642
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A5 gene variants and the risk of coronary heart disease: A case-control study and meta-analysis

Abstract: Previous studies have shown that apolipoprotein A5 (APOA5) gene variants are genetic determinants of the concentration of triglycerides, which are a known risk factor for coronary heart disease (CHD). Using the standardized coronary angiography method, 290 CHD patients and 198 non-CHD controls were recruited from Ningbo Lihuili Hospital. In addition, 331 unrelated healthy volunteers were recruited as healthy controls from Ningbo Ximen Community residents. Three variants of the APOA5 gene, S19W, -1131T>C and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
(82 reference statements)
1
25
0
4
Order By: Relevance
“…We have previously evaluated several polymorphisms associated with the risk of CHD in Chinese [18][19][20][21] . The current study observed significant associations in both men and women, with women being more at risk (men: OR = 1.29, allele p = 0.01, women: OR = 1.64, allele p = 3.92E-04).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously evaluated several polymorphisms associated with the risk of CHD in Chinese [18][19][20][21] . The current study observed significant associations in both men and women, with women being more at risk (men: OR = 1.29, allele p = 0.01, women: OR = 1.64, allele p = 3.92E-04).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the correlation between APOA5 -1131T>C and APOC3 -455T>C SNPs and CHD, we conducted the present meta-analysis and found that both polymorphisms, under both allelic and dominant models, were positively associated with an increased risk of CHD. APOA5 encodes APOA5, a protein consisting of 366 amino acids that is exclusively expressed in human liver tissue and enhances LPL activity (Zhou et al, 2013). The loss of LPL activity interferes with the ability of APOA5 to interact with lipids and lipoproteins, including TGs, VLDLs, and HDLs (Dorfmeister et al, 2008;Johansen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms have been found in the APOC3 gene, including C-482T, T-455C, Sst I, and C1100T. Moreover, accumulating evidence suggests that APOA5 -1131T>C and APOC3 -455T>C polymorphisms play a major role in the development of CHD because of their association with increased plasma TGs (Zhang et al, 2011;Zhou et al, 2013;Cui et al, 2014). On the other hand, many studies have reached contradictory conclusions regarding the role of APOC3 and APOA5 variants in CHD (Martinelli et al, 2007;Maasz et al, 2008;Prochaska et al, 2010;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Literature report that about 50% of their final levels are genetically determined (Hubáček et al, 2009). Numerous studies have reported a significant association between the T1131C APOA5 variant and cardiovascular diseases development, especially myocardial infarction (MI) (Hubáček et al, 2003(Hubáček et al, , 2009Hubacek et al, 2004;Szalai et al, 2004;Zhou et al, 2013;Ouatou et al, 2014). However, this association was not observed in many other studies (Prochaska et al, 2010;Martinelli et al, 2007;Lee et al, 2004).…”
Section: Apoa5mentioning
confidence: 99%